Rumah Mandiri Energi Menggunakan Tenaga Surya dan Biogas - Kunaifi Kunaifi; Devi Nuryadi (UIN Sultan Syarif Kasim Riau, 2011)
A photovoltaic (PV) and a biogas digester systems have been proposed as sources of electrical and gas energy demand for a domestic household in a rural village in Riau Province. PV system was designed using the AS 4509.2-2002 standard, while the biogas digester was designed based on the gas demand for cooking and the minimum number of cattle in each household. With the average solar insolation of 4.2 kWh/m2/day, average daily energy demand of 2.5 kWh, and 362 Watt peak load, the analysis proposed a 900 VA inverter, 6 batteries of 102 Ah, 10 solar modules of 210 Wp, and a BCR of 40 A system. While the biogas system consisted of 4 m3 of biogas digester and 2m3 control digester, with average daily cooking time of 2.4 hours and at least 2 cattle per household. Using the life-cycle cost analysis, the cost of PV system during 20 years period was IDR 113.6 million and the cost of biogas digester for the same period was IDR 8.7 million. Keywords: AS 4509.2-2002, biogas, cattle, solar energy, life-cycle cost analysis.